Method for removing organic matters in water by electrochemical coupling ozone system based on LDH loaded graphite felt cathode

By using LDH-loaded graphite felt cathode in electrochemical coupled ozone technology, the problem of single function of carbon cathode material is solved, efficient generation and utilization of HO• is achieved, and the efficiency of removal of organic matter in water is significantly improved.

CN119569191AActive Publication Date: 2025-03-07INNOVATION CENTER OF YANGTZE RIVER DELTA ZHEJIANG UNIVERSITY

Patent Information

Application Number
CN202411732019.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

In the existing electrochemical coupled ozone technology, the carbon cathode material has a single function and cannot effectively catalyze H2O2 and O3, resulting in low yield and utilization of HO• and it is difficult to efficiently remove organic matter in water.

Method used

An electrochemically coupled ozone system based on the cathode of LDH loaded graphite felt is adopted. Through the load modification of LDH, the generation of H2O2 is inhibited, the generation of O2•- is increased, and the formation of HO• is promoted, thereby improving the removal efficiency of organic matter.

Benefits of technology

It significantly improves the yield and utilization of HO•, enhances the removal effect of organic pollutants, and improves the efficiency and safety of water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569191A_ABST
    Figure CN119569191A_ABST
Patent Text Reader

Abstract

The invention discloses a method for removing organic matters in water based on an electrochemical coupling ozone system of an LDH-loaded graphite felt cathode, which comprises the following steps: taking MFe-LDH / GF as a cathode, taking a platinum sheet as an anode, taking a reaction solution comprising pollutants and an electrolyte, taking Na2SO4 as the electrolyte, adding the two electrodes into the reaction solution, and filling gaseous ozone into the reaction solution, adjusting the pH value of the reaction liquid to 3-9, and charging current into the two electrodes, so as to construct an electrochemical coupling ozone system to remove pollutants. By utilizing the method, the yield of HOO can be improved, so that the removal of organic pollutants is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalytic ozone oxidation and organic matter removal, and specifically relates to a method for removing organic matter in water by using an electrochemically coupled ozone system based on an LDH-loaded graphite felt cathode. Background Art

[0002] With the rapid development of modern industry and the widespread use of chemicals, a large amount of organic wastewater generated by industry, agriculture, medicine and human activities has not been effectively treated. After being discharged into natural water bodies, it has caused serious chemical pollution to available water resources. These synthetic organic pollutants usually have good chemical stability, high toxicity and bioaccumulation, and are difficult to be effectively removed by conventional water treatment processes such as flocculation, filtration and biological action. They often require the use of advanced oxidation and other deep treatment technologies to meet the treatment requirements.

[0003] Electrochemically coupled ozone technology is an emerging advanced oxidation process for water treatment that combines electrochemistry and ozone. The carbon-based cathode in the system can cleverly reduce O2 in the mixed gas produced by the ozone generator to H2O2, thereby inducing a peroxidation reaction between H2O2 and O3 to generate a large amount of HO • , which makes up for the low efficiency of electrochemical oxidation treatment and the poor mineralization rate of ozone oxidation. In addition, compared with electrochemical oxidation, electro-Fenton oxidation and O3 / H2O2 technology, electrochemical coupled ozone not only significantly improves the removal efficiency of pollutants, but also reduces the safety risks of H2O2 in transportation and storage. It is a safer and more convenient water treatment technology.

[0004] The invention patent application with publication number CN113184951A discloses a modification method and application of a graphite felt cathode suitable for an electro-ozonation system. The process includes pre-treatment to remove impurities on the surface of the graphite felt, and anodizing the graphite felt in a neutral sodium sulfate electrolyte, thereby increasing the hydrophilicity of the graphite felt and the content of surface oxygen-containing functional groups, and increasing the active sites for oxygen reduction to hydrogen peroxide. In addition, the production of hydrogen peroxide is increased in the electro-ozonation system, and the removal capacity of oxalic acid is enhanced. It is worth noting that although increasing the content of oxygen-containing functional groups on the surface of graphite felt will lead to an increase in ozone catalytic sites, the modified graphite felt in the electro-ozonation system is protected by the cathode current, which greatly reduces the corrosion damage of ozone to the electrode surface and enhances the stability of the electrode.

[0005] Publication No. CN113371798A discloses a method for removing chemical oxygen demand in wastewater by ozone-coupled electro-Fenton catalysis. In the system for removing chemical oxygen demand in wastewater by electro-Fenton catalysis, a passive anode and iron are used as contact double anodes, and a cathode is graphite felt; or an anode is iron as an anode and a cathode is graphite felt; or a passive anode and a cathode are iron and graphite felt as contact double cathodes, an electro-Fenton system is constructed with sewage to be degraded as electrolyte, a constant direct current is connected externally, and an external ozone generator is used to introduce ozone into the cathode.

[0006] However, compared with the carbon cathode material commonly used in the electrochemical coupled ozone technology disclosed in the above patent application, the function of the carbon cathode material is relatively simple, which only plays the role of generating H2O2, and the H2O2 diffused into the solution will inevitably participate in the HO • Therefore, it is necessary to develop a functional carbon cathode that can catalyze H2O2 and O3 to strengthen the electrochemical coupling of the ozone system HO • improve the yield and utilization rate, and enhance the removal effect of organic pollutants. Summary of the invention

[0007] The present invention provides a method for removing organic matter in water by electrochemically coupled ozone system based on LDH loaded graphite felt cathode, and the method can improve HO • yield, thereby enhancing the removal of organic pollutants.

[0008] The present invention provides a method for removing organic matter in water by an electrochemically coupled ozone system based on an LDH-loaded graphite felt cathode, comprising: MFe-LDH / GF is used as the cathode, wherein M is Cu, Mn, CO or Ni, and a platinum sheet is used as the anode. The reaction solution includes pollutants and an electrolyte, wherein the electrolyte is Na2SO4. Two electrodes are added to the reaction solution, and gaseous ozone is charged into the reaction solution. The pH of the reaction solution is adjusted to 3-9, and current is charged into the two electrodes, thereby constructing an electrochemically coupled ozone system to remove pollutants.

[0009] Preferably, MFe-LDH / GF is used as the cathode, wherein M is Cu. Since Cu has a higher electroactive area, it can more effectively inhibit the generation of H2O2 and generate more O2 •- Reacts with ozone to form more HO • , in order to further improve the removal efficiency of organic matter.

[0010] Preferably, the pH of the reaction solution is 5-7. The present invention controls the pH value of the reaction solution so that an appropriate amount of metal is dissolved to participate in the generation of HO •reaction, while reducing the dissolution of metals due to low pH values, which can cause structural collapse during long-term catalysis and affect the reaction stability.

[0011] Preferably, the density of the current charged into the two electrodes is 2-5 mA / cm 2 .

[0012] Preferably, the concentration of the gaseous ozone is 15-60 mg / L, and the flow rate of the gaseous ozone is 100-300 mL / min.

[0013] Preferably, in the reaction solution, the concentration of Na2SO4 is 30-70 mmol / L, and the concentration of pollutants is 30-60 mg / L.

[0014] Preferably, the pollutant is oxalic acid, pyruvic acid or acetic acid.

[0015] Since the reaction rate of small molecule organic acids (such as oxalic acid, pyruvic acid, acetic acid, etc.) with ozone is extremely low, and they are common degradation products in the process of treating organic wastewater using advanced oxidation technology, which restricts the mineralization degree of organic wastewater, the specific embodiment of the present invention selects oxalic acid as a model pollutant to evaluate the removal efficiency of the electrochemically coupled ozone system for organic matter.

[0016] Preferably, H2SO4 and NaOH are added to the reaction solution to adjust the pH value, the concentration of H2SO4 is 0.05-0.2 mol / L, and the concentration of NaOH is 0.05-0.2 mol / L.

[0017] Preferably, the method for preparing MFe-LDH / GF comprises: Fully dissolving Fe(NO3)3·9H2O, M(NO3)2·xH2O, CO(NH2)2 and NH4F in ultrapure water to obtain LDH mother solution, wherein the mass concentrations of Fe(NO3)3·9H2O, M(NO3)2·xH2O, CO(NH2)2 and NH4F are 9-23 g / L, 13-26 g / L, 20-35 g / L and 1-3 g / L, respectively; Graphite felt is added to the LDH mother liquor to obtain a mixed solution, and the mixed solution is subjected to a hydrothermal reaction at a temperature of 90-120° C. and a reaction time of 8-16 hours. After the reaction is completed, the MFe-LDH / GF is obtained by suction filtration, washing, and drying.

[0018] The present invention controls the reaction temperature and reaction time to fully decompose urea, avoids the collapse of the layered structure caused by too high temperature, and avoids the formation of a large amount of ammonia gas and M ions that are decomposed into a complex, which is not conducive to the formation of the LDH catalyst. The present invention controls the concentration of each substance input to ensure the formation of LDH crystals and reduce impurity generation and metal outflow.

[0019] Preferably, the present invention achieves the best removal effect on organic pollutants by controlling the molar ratio of Fe and M to 2:1 to 3:1, and the mass concentrations of CO(NH2)2 and NH4F to 28.5 g / L and 2.1 g / L, respectively.

[0020] Preferably, the graphite felt is added to the LDH mother liquor, and the surface of the graphite felt is cleaned with acetone and ultrapure water in sequence, and then dried and baked. The above operations are performed to remove oil stains and impurities on the surface of the graphite felt.

[0021] Preferably, the reacted material is repeatedly ultrasonically cleaned with ethanol and ultrapure water until the cleaning solution is neutral.

[0022] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses MFe-LDH / GF as the cathode to inhibit the generation of H2O2 and generate a large amount of O2 •- Instead of H2O2, it reacts with ozone to form HO • , which weakens the effect of H2O2 on HO • At the same time, the present invention controls the pH value of the reaction solution so that part of the metal is dissolved and reacts with ozone to obtain HO • Therefore, based on the above two points, the method provided by the present invention will greatly improve the removal efficiency of organic matter. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 X-ray diffraction patterns of GF and CuFe-LDH / GF cathodes provided in Example 1 of the present invention; Figure 2 The scanning electron microscope image of the CuFe-LDH powder and the CuFe-LDH / GF cathode provided in Example 1 of the present invention; Figure 3 A schematic diagram of a reaction device for an electrochemically coupled ozone system provided in Example 2 of the present invention; Figure 4 A diagram showing the removal effect of oxalic acid by ozone oxidation, anodic oxidation and electrochemically coupled ozone systems with different cathodes provided in Examples 2-5 of the present invention and Comparative Examples 1-2; Figure 5 The electrochemically active areas of different LDH cathodes provided in Examples 2-5 of the present invention; Figure 6This is a graph showing the effect of the quenching agent provided in Example 6 of the present invention on the removal efficiency of oxalic acid; Figure 7 This is a graph showing the effect of the metal molar ratio and preparation temperature on the oxalic acid removal efficiency provided in Example 7 of the present invention; Figure 8 This is a diagram showing the effect of solution pH on oxalic acid removal efficiency provided in Example 8 of the present invention; Fig. 9 The stability of OA removal by the EP system with CuFe-LDH / GF as cathode provided in Example 9 of the present invention; Fig.10 This is a diagram showing the removal effect of dissolved organic carbon in nanofiltration concentrate by ozone oxidation and electrochemically coupled ozone systems with different cathodes provided in Example 10 of the present invention.

[0024] Specific embodiment The layered double hydroxide (LDH) used in the specific embodiment of the present invention is a type of octahedral two-dimensional layered clay structure with multiple metal layers and adjustable interlayer anions, and is widely used in the fields of catalysis, adsorption and drug delivery. Therefore, the use of LDH-loaded carbon cathode with high catalytic activity and large specific surface area helps to enhance the utilization efficiency of H2O2 and O3 in the electrochemically coupled ozone system, promote the formation of active species, and accelerate the removal of organic pollutants.

[0025] The present invention is further described and illustrated below in conjunction with the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly without conflicting with each other.

[0026] Example 1 A CuFe-LDH / GF cathode suitable for an electrochemically coupled ozone system comprises the following synthesis steps: (1) Cut the purchased commercial graphite felt into 2 cm × 4 cm pieces and wash them with acetone and ultrapure water for 20 min respectively to remove surface oil and impurities. Then put them into a constant temperature drying oven at 60 °C and dry them for 24 h before use.

[0027] (2) Dissolve 0.808 g Fe(NO3)3·9H2O, 1.449 g Cu(NO3)2·3H2O, 2 g CO(NH2)2 and 0.247 g NH4F in 70 mL of ultrapure water to obtain LDH mother solution.

[0028] (3) Immerse the spare graphite felt in step (1) in the LDH mother liquor in step (2), discharge the bubbles in the pores of the graphite felt, then transfer the LDH mother liquor and the graphite felt to a stainless steel reactor containing a polytetrafluoroethylene liner, put it into an oven, set the reaction temperature and time to 90°C and 12 h, respectively, separate the LDH powder and the LDH-loaded graphite felt by suction filtration after the reaction, and repeatedly ultrasonically clean the material with ethanol and ultrapure water until the cleaning solution is neutral, and place the cleaned LDH-loaded graphite felt in a vacuum drying oven at 50°C to dry, which is represented by CuFe-LDH / GF. The cathode has the following characteristics:

[0029] like Figure 1 As shown in the figure, the diffraction peak at 26.3° belongs to the 002 plane of graphite felt (GF), and the diffraction peaks at 11.5°, 23.1°, 34.1° and 38.7° correspond to the (003), (006), (012) and (015) crystal planes of the CuFe-LDH / GF cathode, respectively, indicating that CuFe-LDH was successfully synthesized and loaded on the surface of graphite felt. In addition, Cu2(OH)2CO3 crystals (JCPDF#01-072-8421) were also found in the CuFe-LDH / GF cathode. This is because urea releases CO2 while providing an alkali source during the hydrothermal synthesis process, resulting in the combination of metal ions and carbonates, thereby forming a malachite structure. Figure 2 (a) and (b) show that the CuFe-LDH powder presents a typical layered structure, and after being loaded on graphite felt, it presents small particle flakes, further indicating that the CuFe-LDH / GF cathode was successfully synthesized.

[0030] Table 1 shows the specific surface area and pore parameters of GF and CuFe-LDH / GF. It can be seen that after GF was modified by CuFe-LDH loading, the BET specific surface area increased by 0.61 m 2 / g, which is beneficial to improve the adsorption capacity of the cathode. In addition, the average pore diameter of GF is small, mainly micropores, while the average pore diameter of CuFe-LDH / GF is large, which is beneficial for the diffusion of reactants to the catalytic site and promotes the mass transfer efficiency between the cathode and the solution.

[0031] Table 1 Specific surface area and pore parameters GF CuFe-LDH / GF <![CDATA[BET(m 2 / g)]]> 0.96 1.57 <![CDATA[Micropore area (m 2 / g)]]> 0.66 0.69 <![CDATA[Total pore volume (cm 3 / g)]]> 0.0014 0.0070 Average pore diameter (nm) 5.73 17.80 Example 2 This example investigates the removal effect of oxalic acid by the electrochemically coupled ozone system with CuFe-LDH / GF as the cathode. Figure 3. The ozone generator uses high-purity oxygen as the gas source. The generated gas phase O3 is analyzed by the ozone detector for concentration and then passed into the reaction tank through the microporous aeration head. A magnetic stirrer is used to evenly dissolve the gas phase O3 in the reaction liquid, and a water bath is used to control the reaction temperature. The gas outlet of the reaction tank is connected to an ozone decomposer to destroy the undissolved gas phase O3. A DC power supply is used to provide a constant current density. All gas ducts in the reaction device are made of ozone-resistant rubber tubes. Specifically, the following steps are included:

[0032] (1) The CuFe-LDH / GF in Example 1 was used as a cathode and a platinum sheet (2×4 cm) was used as an anode. The distance between the cathode and the anode was 2 cm.

[0033] (2) The reaction solution volume was 400 mL, which contained 30 mg / L oxalic acid and 50 mmol / L Na2SO4. The initial pH of the solution was adjusted to 7 using 0.1 mol / L H2SO4 and 0.1 mol / L NaOH. The gas phase ozone concentration was adjusted to 30 mg / L and the gas flow rate was adjusted to 200 mL / min. -1 , the water bath temperature was adjusted to 25°C.

[0034] (3) Use a DC power supply to provide a current density of 2 mA / cm 2 , set the power-on time to 20 min, extract 1 mL of reaction solution at the preset time, and detect the remaining oxalic acid concentration in the water by high performance liquid chromatography.

[0035] like Figure 4 As shown, the removal rate of oxalic acid in this embodiment is 91.2%.

[0036] Comparative Example 1 like Figure 4 As shown, without turning on the ozone generator, the remaining steps are consistent with Example 2. It is almost impossible to remove oxalic acid within 20 minutes by relying solely on the oxidation of the platinum anode. Without applying current, the remaining steps are consistent with Example 2. Only 7.0% of oxalic acid can be removed within 20 minutes by relying on the oxidation of ozone. The results show that the removal effect of oxalic acid by the electrochemically coupled ozone system with CuFe-LDH / GF as the cathode is much higher than the sum of the efficiencies of the single anodic oxidation and the single ozone oxidation.

[0037] Comparative Example 2 like Figure 4 As shown, the graphite felt (GF) in step 1 of Example 1 is used instead of the CuFe-LDH / GF cathode, and the remaining steps are consistent with Example 2. 46.8% of oxalic acid can be removed within 20 min, but it is much lower than the electrochemically coupled ozone system with CuFe-LDH / GF as the cathode.

[0038] Example 3-Example 5 In Example 3-Example 5, MnFe-LDH / GF, CoFe-LDH / GF and NiFe-LDH / GF were used as cathodes instead of CuFe-LDH / GF in Example 2. The electrochemically coupled ozone systems constructed in Example 3-Example 5 all showed good oxalic acid removal capabilities, but were still lower than the electrochemically coupled ozone system with CuFe-LDH / GF as the cathode, indicating that the divalent metal selection of the LDH-loaded graphite felt cathode in the system would affect the removal efficiency of oxalic acid. Figure 5 (a)-(f) Cyclic voltammetry curves at different scan rates show that the CuFe-LDH / GF cathode has the highest double-layer capacitance (10200 μF) among the four Fe-based LDH cathodes, indicating that it has the highest electroactive area, which is conducive to the occurrence of cathode reduction reactions and the formation of active species.

[0039] The preparation methods of the MnFe-LDH / GF, CoFe-LDH / GF and NiFe-LDH / GF cathodes are similar to the preparation method of the CuFe-LDH / GF cathode. According to the molar ratio of divalent metals (such as Cu, Mn, Co, Ni) to trivalent metals (Fe) in the LDH preparation process of 0.006 mol: 0.002 mol, the Cu(NO3)2·3H2O in Example 1 was replaced by 1.506 g of Mn(NO3)2·4H2O, 1.746 g of Co(NO3)2·6H2O and 1.744 g of Ni(NO3)2·6H2O, respectively.

[0040] Example 6 This example explores the mechanism of removing oxalic acid by an electrochemically coupled ozone system with CuFe-LDH / GF as the cathode, which specifically includes the following steps: (1) The CuFe-LDH / GF in Example 1 was used as a cathode and a platinum sheet (2×4 cm) was used as an anode. The distance between the cathode and the anode was 2 cm.

[0041] (2) The reaction solution volume was 400 mL, which contained 30 mg / L oxalic acid and 50 mmol / L Na2SO4 as electrolytes. The initial pH of the solution was adjusted to 7 using 0.1 mol / L H2SO4 and 0.1 mol / L NaOH. The gas phase ozone concentration was adjusted to 30 mg / L and the gas flow rate was adjusted to 200 mL / min. -1 , the water bath temperature was adjusted to 25°C. 20 mmol / L tert-butyl alcohol was added as HO • quencher, 20 mmol / L chloroform as O2 •- quencher.

[0042] (3) Use a DC power supply to provide a current density of 2 mA / cm 2 , set the power-on time to 20 min, extract 1 mL of reaction solution at the preset time, and detect the remaining oxalic acid concentration in the water by high performance liquid chromatography.

[0043] like Figure 6 As shown in Figure 2, after adding 20 mmol / L TBA to the system, the degradation efficiency of oxalic acid was significantly inhibited, and the removal rate dropped from 91.2% to 13.2%, indicating that HO • It is the main active species for degrading oxalic acid. After adding 20 mmol / L chloroform to the system, the removal rate of oxalic acid decreased by 61.6%, indicating that O2 •- It is also an important active species in the degradation of oxalic acid. •- The redox potential of oxalic acid is only 1.0 V, which is almost incapable of oxidizing oxalic acid. • It plays an extremely important role in the formation process.

[0044] In addition, when only O2 and current were applied without ozone, the GF cathode could generate 11 mg / L of H2O2 within 20 min, while the H2O2 production of the CuFe-LDH / GF cathode was only 1.6 mg / L. The above results indicate that the loading of CuFe-LDH changes the reduction path of O2 on the GF cathode, and the O2 generated on the cathode •- Instead of H2O2, it reacts with ozone to form HO • (Formula 1-3), which weakens the effect of H2O2 on HO • The quenching effect of oxalic acid was greatly improved.

[0045] (1) (2) (3) Example 7 This example investigates the effect of the preparation parameters of the CuFe-LDH / GF cathode on the removal of oxalic acid, and specifically includes the following steps: (1) The steps in Example 1 were used to prepare CuFe-LDH / GF cathodes (total metal content was 0.008 mol) with different molar ratios of Cu and Fe. Except for the different amounts of metal salts added during the preparation of LDH mother solution, the other steps were the same. When the molar ratios of Cu and Fe were 0:1, 1:1, 2:1, 3:1, 4:1, and 1:0, the amounts of Fe(NO3)3·9H2O and Cu(NO3)2·3H2O added were 3.232 g and 0 g, 1.616 g and 0.966 g, 1.077 g and 1.288 g, 0.808 g and 1.449 g, 0.646 g and 1.546 g, and 0 g and 1.933 g, respectively.

[0046] (2) The steps in Example 1 were used to prepare CuFe-LDH / GF cathodes with different synthesis temperatures. Except that the synthesis temperatures were 70°C, 90°C, 120°C, and 140°C, the remaining steps were the same.

[0047] (3) The CuFe-LDH / GF prepared in this example was used as the cathode, and the platinum sheet (2×4 cm) was used as the anode. The distance between the cathode and the anode was 2 cm. The reaction solution volume was 400 mL, which contained 30 mg / L oxalic acid and 50 mmol / L Na2SO4 as electrolytes. The initial pH of the solution was adjusted to 7 using 0.1 mol / L H2SO4 and 0.1 mol / L NaOH. The gas phase ozone concentration was adjusted to 30 mg / L, and the gas flow rate was adjusted to 200 mL / min. -1 , the water bath temperature was adjusted to 25°C.

[0048] (4) Use a DC power supply to provide a current density of 2 mA / cm 2 , set the power-on time to 20 min, extract 1 mL of reaction solution at the preset time, and detect the remaining oxalic acid concentration in the water by high performance liquid chromatography.

[0049] like Figure 7 As shown in the figure, under the condition of keeping the total amount of metal unchanged during the preparation process, the GF cathode loaded with Cu or Fe alone has a relatively poor effect on removing oxalic acid in the electrochemically coupled ozone system, which is 75.4% and 78.8%, respectively, but is still higher than the unloaded GF cathode (46.8%). When the two metal elements are added, the molar ratio of Cu to Fe is 2:1 or 3:1, which is consistent with the optimal M reported in the literature. 2+ With M 3+The ratio of oxalic acid is consistent. As the preparation temperature increased from 70°C to 120°C, the removal rate of oxalic acid increased from 67.8% to more than 90%. This is because the higher preparation temperature can accelerate the decomposition of urea and cause the pH of the solution to rise rapidly, thereby more effectively forming the LDH catalyst. Further increasing the temperature to 140°C will significantly reduce the removal rate of oxalic acid. This may be because the high temperature causes the collapse of the layered structure, thereby affecting the catalytic activity of LDH. In addition, during the preparation process, it was found that when the temperature was 90°C or 120°C, the filtrate after the preparation was colorless, while the filtrate at 140°C was dark blue. This is because the high temperature causes urea to decompose a large amount of ammonia (NH3), which eventually forms a copper-ammine complex ([Cu(NH3)4] 2+ ), which is not conducive to the formation of LDH catalyst. Therefore, the optimal Cu:Fe molar ratio of CuFe-LDH / GF cathode is 3:1, and the optimal hydrothermal temperature is 120℃.

[0050] Example 8 Since solution pH is a key influencing factor in the electrochemically coupled ozone system, this example investigates the effect of solution pH on oxalic acid removal in an electrochemically coupled ozone system using CuFe-LDH / GF as the cathode, specifically comprising the following steps: (1) The CuFe-LDH / GF in Example 1 was used as a cathode and a platinum sheet (2×4 cm) was used as an anode. The distance between the cathode and the anode was 2 cm.

[0051] (2) The reaction solution volume was 400 mL, which contained 30 mg / L oxalic acid and 50 mmol / L Na2SO4 as electrolytes. The initial pH of the solution was adjusted to 3-11 using 0.1 mol / L H2SO4 and 0.1 mol / L NaOH. The gas phase ozone concentration was adjusted to 30 mg / L and the gas flow rate was adjusted to 200 mL / min. -1 , the water bath temperature was adjusted to 25°C.

[0052] (3) Use a DC power supply to provide a current density of 2 mA / cm 2 , set the power-on time to 20 min, extract 1 mL of reaction solution at the preset time, and detect the remaining oxalic acid concentration in the water by high performance liquid chromatography.

[0053] like Figure 8 As shown in the figure, when the initial pH of the solution is 3.0, the removal rate of oxalic acid by the system of the present invention is close to 100% within 20 minutes. As the pH of the solution increases to 5.0-9.0, the removal rate of oxalic acid is 86.0%-92.6%. When the initial pH of the solution increases to 11.0, the removal rate of oxalic acid is only about 20%, which is because O3 is difficult to accumulate and CO3 2- HO• In general, the system of the present invention exhibits good oxalic acid removal ability in the solution pH range of 3.0-9.0, improving the problem of poor performance of conventional electrochemical coupling systems under acidic conditions.

[0054] Example 9 This example investigates the stability of the electrochemically coupled ozone system with CuFe-LDH / GF as the cathode in removing oxalic acid, which specifically includes the following steps: (1) The CuFe-LDH / GF in Example 1 was used as a cathode and a platinum sheet (2×4 cm) was used as an anode. The distance between the cathode and the anode was 2 cm.

[0055] (2) The reaction solution volume was 400 mL, which contained 30 mg / L oxalic acid and 50 mmol / L Na2SO4 as electrolytes. The initial pH of the solution was adjusted to 7.0 using 0.1 mol / L H2SO4 and 0.1 mol / L NaOH. The gas phase ozone concentration was adjusted to 30 mg / L and the gas flow rate was adjusted to 200 mL / min. -1 , the water bath temperature was adjusted to 25°C.

[0056] (3) Use a DC power supply to provide a current density of 2 mA / cm 2 , set the power-on time to 20 min, extract 1 mL of reaction solution at the preset time, and detect the remaining oxalic acid concentration in the water by high performance liquid chromatography.

[0057] like Fig. 9 As shown in the figure, after the CuFe / GF cathode was reused for 5 times, the removal rate of oxalic acid did not decrease significantly. In addition, the leaching amounts of Cu and Fe in the repeated experiments were all <0.06 mg·L -1 , meeting the national "Sanitary Standard for Drinking Water" (GB5749-2022). The excellent stability of the EP-CuFe / GF system can be attributed to two aspects: on the one hand, the Ksp of Cu or Fe hydroxide in LDH is high and it is not easy to dissolve under neutral conditions; on the other hand, due to the effect of cathodic protection, the surface structure of the CuFe / GF cathode is not easily destroyed by O3. Therefore, EP-CuFe / GF can continuously and efficiently degrade oxalic acid under neutral conditions, which lays the foundation for the practical application of this technology.

[0058] Example 10 This example investigates the removal effect of an electrochemically coupled ozone system with CuFe-LDH / GF as the cathode on actual wastewater, specifically comprising the following steps: (1) The CuFe-LDH / GF in Example 1 was used as a cathode and a platinum sheet (2×4 cm) was used as an anode. The distance between the cathode and the anode was 2 cm.

[0059] (2) Municipal nanofiltration concentrated water was selected as the target wastewater, and its basic physical and chemical properties are shown in Table 2. The reaction liquid volume was 400 mL, the gas phase ozone concentration was adjusted to 30 mg / L, and the gas flow rate was adjusted to 200 mL / min. -1 , the water bath temperature was adjusted to 25°C.

[0060] Table 2 Basic physical and chemical properties of municipal nanofiltration concentrate index parameter index parameter Water temperature / ℃ 15 Chroma / degree < 5 Turbidity / NTU 0.032 pH 7.7 Visible to the naked eye none <![CDATA[UV 254 ]]> 0.184 <![CDATA[DOC(mg·L -1 )]]> 16.38 <![CDATA[Conductivity (μs·cm -1 ).]]> 1191 <![CDATA[Inorganic carbon (mg·L -1 ).]]> 44.52 Redox potential (mV) -57 (3) Use a DC power supply to provide a current density of 2 mA / cm 2 , set the power-on time to 20 min, extract 5 mL of reaction solution at the preset time, and use the TOC analyzer to detect the remaining total dissolved organic carbon (DOC) in the water.

[0061] like Fig.10 As shown in the figure, within 60 min of treatment time, the removal rates of DOC by ozone oxidation, electrochemically coupled ozone system with GF as cathode, and electrochemically coupled ozone system with CuFe-LDH / GF as cathode were 35.9%, 53.1%, and 61.6%, respectively. The results show that the system of the present invention has a high organic matter removal capacity in actual wastewater treatment and shows good practical application potential.

[0062] In summary, the electrochemically coupled ozone system based on CuFe-LDH loaded graphite felt cathode proposed in the present invention effectively combines the advantages of electrochemical oxidation and ozone oxidation, makes up for the shortcomings of low electrochemical oxidation treatment efficiency and poor ozone oxidation mineralization rate, and weakens the effect of H2O2 on HO in conventional electrochemically coupled ozone system. • The quenching effect of HO • It is a relatively clean and efficient advanced oxidation technology for water treatment.

[0063] In the electrochemically coupled ozone system, there are relatively few studies on the functional modification of carbon cathodes, and they are mainly focused on the loading of nanocarbon materials or metal oxides, which often require high-temperature calcination processes and may cause secondary pollution and material deformation. The loading modification of LDH in the method of the present invention adopts a mild hydrothermal synthesis method, which is relatively simple and the synthesized cathode material is relatively stable.

[0064] The graphite felt cathode material used in the method provided in the specific embodiment of the present invention is inexpensive and easy to obtain. The modified graphite felt cathode maintains good stability in the system. After being recycled for 5 times, the removal efficiency of oxalic acid remains above 90%, and the mass concentration of leached Fe and Cu elements is less than < 0.06 mg / L, which is lower than the national "Sanitary Standard for Drinking Water" (GB5749-2022).

[0065] Compared with electrochemical oxidation, ozone oxidation and the electrochemically coupled ozone system with unmodified graphite felt as the cathode, the electrochemically coupled ozone system based on the CuFe-LDH / GF cathode used in the present method has a significant improvement in the removal rate of organic matter.

[0066] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for removing organic matter from water using an electrochemically coupled ozone system based on an LDH-loaded graphite felt cathode, characterized in that: include: MFe-LDH / GF is used as the cathode, where M is Cu, Mn, CO or Ni, and a platinum sheet is used as the anode. The reaction solution includes pollutants and an electrolyte, and the electrolyte is Na2SO4. Two electrodes are added to the reaction solution, and gaseous ozone is charged into the reaction solution. The pH of the reaction solution is adjusted to 3-9, and current is charged into the two electrodes to construct an electrochemically coupled ozone system to remove pollutants.

2. The method for removing organic matter from water using an electrochemically coupled ozone system based on an LDH-loaded graphite felt cathode according to claim 1, characterized in that: MFe-LDH / GF was used as the cathode, where M was Cu.

3. The method for removing organic matter from water using an electrochemically coupled ozone system based on an LDH-loaded graphite felt cathode according to claim 1, characterized in that: The pH of the reaction solution is 5-7.

4. The method for removing organic matter from water using an electrochemically coupled ozone system based on an LDH-loaded graphite felt cathode according to claim 1, characterized in that: The density of the current charged to the two electrodes is 2-5 mA / cm 2 .

5. The method for removing organic matter from water using an electrochemically coupled ozone system based on an LDH-loaded graphite felt cathode according to claim 1, characterized in that: The concentration of the gaseous ozone is 15-60 mg / L, and the flow rate of the gaseous ozone is 100-300 mL / min.

6. The method for removing organic matter from water using an electrochemically coupled ozone system based on an LDH-loaded graphite felt cathode according to claim 1, characterized in that: In the reaction solution, the concentration of Na2SO4 is 30-70 mmol / L, and the concentration of pollutants is 30-60 mg / L.

7. The method for removing organic matter from water using an electrochemically coupled ozone system based on an LDH-loaded graphite felt cathode according to claim 1 or 6, characterized in that: The pollutant is oxalic acid, pyruvic acid or acetic acid.

8. The method for removing organic matter from water using an electrochemically coupled ozone system based on an LDH-loaded graphite felt cathode according to claim 1, characterized in that: H2SO4 and NaOH were added to the reaction solution to adjust the pH value, wherein the concentration of H2SO4 was 0.05-0.2 mol / L, and the concentration of NaOH was 0.05-0.2 mol / L.

9. The method for removing organic matter from water using an electrochemically coupled ozone system based on an LDH-loaded graphite felt cathode according to claim 1, characterized in that: The preparation method of the MFe-LDH / GF comprises: Fe(NO3)3·9H2O, M(NO3)2·3H2O, CO(NH2)2 and NH4F are fully dissolved in ultrapure water to obtain LDH mother solution, wherein the mass concentrations of Fe(NO3)3·9H2O, M(NO3)2·3H2O, CO(NH2)2 and NH4F are 9-23 g / L, 13-26 g / L, 20-35 g / L and 1-3 g / L, respectively; Graphite felt is added to the LDH mother liquor to obtain a mixed solution, and the mixed solution is subjected to a hydrothermal reaction at a temperature of 90-120° C. and a reaction time of 8-16 hours. After the reaction is completed, the MFe-LDH / GF is obtained by suction filtration, washing, and drying.

10. The method for removing organic matter from water using an electrochemically coupled ozone system based on an LDH-loaded graphite felt cathode according to claim 1, characterized in that: Graphite felt was added into LDH mother liquor, and the surface of the graphite felt was cleaned with acetone and ultrapure water in sequence, and then dried and baked.

Citation Information

Patent Citations

  • Modification method suitable for graphite felt cathode in electric peroxone oxidation system and application

    CN113184951A

  • Method for removing bromate in water body by using FeAl layered metal hydroxide modified graphite felt electrode

    CN115010216A

  • Zinc-free dendritic carbon fiber negative electrode material based on flat MgAl-LDH and battery and method thereof

    CN117712390A

  • Optically transparent oxygen generation catalyst, production method thereof, and chemical reactor utilizing the same

    US20180073153A1

  • Dual electrolyte approach to increase energy density of aqueous metal-based batteries

    US20230031554A1

Cited By

  • Double-chamber decoupling water treatment method and device based on graphite blanket loaded cobalt manganese oxide composite material

    CN121554054A